Heparin-Binding Epidermal Growth Factor-Like Growth Factor in Hippocampus: Modulation of Expression by Seizures and Anti-Excitotoxic Action - Opanashuk, Lisa A. (J Neurosci, 1999)
The expression of heparin-binding epidermal growth factor-like growth factor (HB-EGF), an EGF receptor ligand, was investigated in rat forebrain under basal conditions and after kainate-induced excitotoxic seizures. In addition, a potential neuroprotective role for HB-EGF was assessed in hippocampal cultures. In situ hybridization analysis of HB-EGF mRNA in developing rat hippocampus revealed its expression in all principle cell layers of hippocampus from birth to postnatal day (P) 7, whereas from P14 through adulthood, expression decreased in the pyramidal cell layer versus the dentate gyrus granule cells. After kainate-induced excitotoxic seizures, levels of HB-EGF mRNA increased markedly in the hippocampus, as well as in several other cortical and limbic forebrain regions. In the hippocampus, HB-EGF mRNA expression increased within 3 hr after kainate treatment, continued to increase until 24 hr, and then decreased; increases occurred in the dentate gyrus granule cells, in the molecular layer of the dentate gyrus, and in and around hippocampal pyramidal CA3 and CA1 neurons. At 48 hr after kainate treatment, HB-EGF mRNA remained elevated in vulnerable brain regions of the hippocampus and amygdaloid complex. Western blot analysis revealed increased levels of HB-EGF protein in the hippocampus after kainate administration, with a peak at 24 hr. Pretreatment of embryonic hippocampal cell cultures with HB-EGF protected neurons against kainate toxicity. The kainate-induced elevation of [Ca(2+)](i) in hippocampal neurons was not altered in cultures pretreated with HB-EGF, suggesting an excitoprotective mechanism different from that of previously characterized excitoprotective growth factors. Taken together, these results suggest that HB-EGF may function as an endogenous neuroprotective agent after seizure-induced neural activity/injury.